Allergic diseases of the eye (W.B. Saunders Co., 2001)
Harvard Medical School, Boston, MA. Revised reprint of Allergic Diseases of the Eye, c2000, a Brandon/Hill Medical List selection (#379). Addresses relevant new developments in the field of ocular allergy. Discusses clinical manifestations and treatments available now and in the near future. First edition listed week 2000-23. DNLM: Eye Diseases--Immunology.